Fault location scheme of HVDC converter based on fault loop analysis - Dalin Mu; Guo Lei; Tingwei Xu; Haiqiang Zhang; Xiaopeng Li; Sheng Lin (International Journal of Electrical Power & Energy Systems)
In order to solve the problem that multiple faults in the converter area will trigger the valve short-circuit protection action, and the fault location cannot be directly located according to the protection action result, a novel converter fault location method based on fault loop analysis is proposed. The fault characteristics of electrical quantity of 11 kinds of faults in the converter area under the valve short-circuit protection action are analyzed. It was found that the spatiotemporal difference of current and voltage under the converter valve blocking state is obvious when the faults occur in different locations. Based on this, a location criterion based on the integral feature of electrical quantity is designed to identify the fault positions in the converter area. The simulation model of a ± 800 kV UHVDC system is established. The verification results show that the proposed fault location method can accurately locate 11 typical faults in the converter area, which including AC side grounding/short-circuit faults, valve arm short-circuit faults, DC side grounding/short-circuit faults. The proposed method does not need to add additional measurement points, which has obvious engineering application prospects.